Рубежи славы - Мощанский Илья Борисович (Забытые страницы Второй мировой, 2010)
Экземпляры: (201012) / Инвентарный номер: 46471 / Цена: 134.97 / Сис.шифр: 63.3(2)622.1 46471 / Авт.знак: М 87 / ББК: 63.3(2)622.1